LDLR dysfunction induces LDL accumulation and promotes pulmonary fibrosis - Shi, Xiangguang; Chen, Yahui; Liu, Qingmei; Mei, Xueqian; Liu, Jing; Tang, Yulong; Luo, Ruoyu; Sun, Dayan; Ma, Yanyun; Wu, Wenyu; Tu, Wenzhen; Zhao, Yinhuan; et al. (Clinical and Translational Medicine, 2022)
Treatments for pulmonary fibrosis (PF) are ineffective because its molecular pathogenesis and therapeutic targets are unclear. Here, we show that the expression of low-density lipoprotein receptor (LDLR) was significantly decreased in alveolar type II (ATII) and fibroblast cells, whereas it was increased in endothelial cells from systemic sclerosis-related PF (SSc-PF) patients and idiopathic PF (IPF) patients compared with healthy controls. However, the plasma levels of low-density lipoprotein (LDL) increased in SSc-PF and IPF patients. The disrupted LDL-LDLR metabolism was also observed in four mouse PF models. Upon bleomycin (BLM) treatment, Ldlr-deficient (Ldlr-/-) mice exhibited remarkably higher LDL levels, abundant apoptosis, increased fibroblast-like endothelial and ATII cells and significantly earlier and more severe fibrotic response compared to wild-type mice. In vitro experiments revealed that apoptosis and TGF-beta 1 production were induced by LDL, while fibroblast-like cell accumulation and ET-1 expression were induced by LDLR knockdown. Treatment of fibroblasts with LDL or culture medium derived from LDL-pretreated endothelial or epithelial cells led to obvious fibrotic responses in vitro. Similar results were observed after LDLR knockdown operation. These results suggest that disturbed LDL-LDLR metabolism contributes in various ways to the malfunction of endothelial and epithelial cells, and fibroblasts during pulmonary fibrogenesis. In addition, pharmacological restoration of LDLR levels by using a combination of atorvastatin and alirocumab inhibited BLM-induced LDL elevation, apoptosis, fibroblast-like cell accumulation and mitigated PF in mice. Therefore, LDL-LDLR may serve as an important mediator in PF, and LDLR enhancing strategies may have beneficial effects on PF.
CRIS-Team WoS Importer:2022-02-11
Keywords: apoptosis; combination treatment; LDL; LDLR; pulmonary fibrosis